School for extraterrestrial girls. 2, Girls in flight - Whitley, Jeremy (Whitley, Jeremy. School for extraterrestrial girls, 2023)
"The extraterrestrial girls are back! With their former school compromised, exposing Tara, Misako, Summer, and Kat, to possible danger from unknown alien forces, they all must relocate to a new hidden school--The School for Extraterrestrial Boys! Located on a hidden island in the arctic north, the new campus has a mysteriously warm summer climate, a beautiful lake, and dozens of sinister mysteries! The girls are staying in what appears to be summer cabins on the lake while going to school in the mysterious castle where the boys stay. This is all under the watchful eye of the boys' headmaster, Headmaster Stokes--an arrogant man with an unknown agenda and an obsession with Tara's people. They may still be in school, but this will be a semester full of blossoming romances, learning to love themselves, and trying to survive the mysteries of both this terrifying island and boys! Romance, magic, and near-death experiences are all part of a regular school day at the School for Extraterrestrial Girls."--